Serum endoglin as a marker in hepatocellular carcinoma - Rehab A Mohamed; Hend M Maghraby; Eman M Abd El Salam; Hala M Nageb; Eman E Ahmad; Nagwa A Mohamed (SpringerOpen, 2015)
Introduction Hepatitis C viral (HCV) infection is a major risk factor for liver cirrhosis, liver failure, and hepatocellular carcinoma (HCC). A number of laboratory-based methods has been developed for the noninvasive diagnostic evaluation of HCC. Endoglin (CD105) is a homodimeric membrane glycoprotein expressed on endothelial cells that can bind to transforming growth factor-b1 and transforming growth factor-b3. Aim of the study The aim of this study was to evaluate the diagnostic value of endoglin and alpha-fetoprotein (AFP) in patients with chronic HCV infection with and without HCC. Patients and methods A total of 50 HCV patients were chosen and divided into two groups, group I (26 cirrhotic patients) and group II (24 HCC patients), and compared with group III (10 healthy volunteers) as controls. For all participants, thorough clinical examination, blood picture, liver function tests, HCV antibody, AFP, and serum endoglin were performed. Abdominal ultrasound, abdominal triphasic computed tomographic (CT) scan, and liver biopsy for those diagnosed HCC by triphasic CT were performed. Results We found highly significant increase in serum endoglin in HCV patients with HCC (group II) compared with HCV patients with liver cirrhosis (group I) and controls (group III). There was significant positive correlation between serum endoglin and aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total bilirubin, and AFP. In addition, there was significant negative correlation between serum endoglin and hemoglobin, albumin, and prothrombin concentration. The cutoff value for serum AFP for which HCC is suspected was greater than 250 ng/ml with sensitivity 79% and specificity 89%, whereas the cutoff value for serum endoglin was greater than 10.57 ng/ml with sensitivity 70% and specificity 81%. Conclusion Serum Endoglin is a promising tumor marker that may be used with serum AFP as noninvasive technique to aid diagnosis of HCC.